Statins and other lipid-lowering therapy and pregnancy outcomes in homozygous familial hypercholesterolaemia – a retrospective review of 39 pregnancies. - Botha, Theunis Christoffel (My University, 2018)
BACKGROUND: Pregnancy in homozygous familial hypercholesterolaemia (HoFH) females is associated with further elevation of already markedly elevated low density lipoprotein cholesterol (LDL-C) levels, particularly if lipid-lowering therapy is discontinued, placing the mother and fetus at increased cardiovascular risk. Lipoprotein apheresis (LA) is the current recommended treatment for pregnant HoFH patients. However, this is costly, time consuming, and is not available in many countries. Alternative treatment strategies to control hypercholesterolaemia during pregnancy in HoFH patients are necessary. The aim of this study was to assess pregnancy outcomes in a cohort of female HoFH patients, many of whom received statins with or without other lipid lowering therapy. METHODS: This study was a retrospective review of 39 pregnancies from a cohort of 20 genotypically confirmed female HoFH patients. Demographic, clinical, laboratory and treatment information, particularly the use of medication during pregnancy, was extracted from hospital files. Either patients themselves or a close, surviving family member were contacted directly to obtain informed consent for anonymized data collection and additional information. We compared birth weights of statin exposed and statin unexposed infants with the Mann Whitney U test and utilized a one tailed t-test to compare lipid levels, prior to, and following pregnancy. We considered p <0.05 significant RESULTS: No maternal cardiac complications or deaths occurred during the pregnancies or during the first year postpartum. Twenty-five pregnancies were exposed to lipid-lowering therapy, of which 18 were exposed to statin therapy, just prior to or during the pregnancy. Thirty-three (84%) pregnancies carried to term, 3 (8%) premature deliveries and 3 (8%) miscarriages were observed. Complications associated with pregnancy in these HoFH patients, did not differ from those reported during pregnancies of otherwise healthy woman. CONCLUSION: HoFH is a severe disease impacting significantly on life expectancy. However, for many females with HoFH, despite the high cardiovascular risk, pregnancy is not uncommon. In resource poor settings and when LA is not available, lipid lowering therapy, particularly statin therapy during pregnancy, appears to be safe for both mother and fetus and is an acceptable alternative for LDL-C reduction in these high risk patients.
A research report submitted to the University of the Witwatersrand in fulfilment of the requirement for the degree of Master of Medicine, Johannesburg November 2018
Keywords: Hypercholesterolemia; Pregnancy